Development of a chitosan based glucose responsive nanoparticulate insulin delivery system - Yaa, Asantewaa (2014)
Research into responsive polymeric insulin delivery systems for the management of diabetes mellitus is gaining increasing interest due to the rise in the incidence rate and the burden of daily multiple subcutaneous insulin injections that needs to be endured by the patient. The present study attempted to formulate a nanoparticulate glucose responsive insulin delivery system from a natural polymer chitosan, using a safe glucose sensor, phenyl boronic acid (PBA), which is known to interact with glucose. In the present project, a new method for the production of chitosan tripolyphosphate (TPP) nanoparticles via ultrasonication was developed and optimised. The electrostatic method of tagging PBA onto chitosan was unsuccessful, but the method of N-reductive alkylation of introducing the PBA was successful. Evidence of PBA bonding on to chitosan was assessed by FTIR, ToF-SIMS, DSC and glucose adsorption sensitivity measurements. Glucose adsorption sensitivity to PBA-bonded chitosan polymer was directly related to the amount of PBA functionality within the conjugates and the physical nature of the matrices (porous or crystalline) as revealed by scanning electron microscopy (SEM). The nanoparticles showed glucose concentration dependent swelling with swelling decrease at a glucose concentration above 2.5mg/ml. Encapsulation of insulin into the nanoparticulate matrix was achieved by both the ionotropic gelation and polyelectrolyte complexation methods. Smaller particles with z-average between 140 – 150nm, lower Pdi and zeta potential between 17.5-19.1mV were characteristic of particles produced by PEC, whilst slightly larger particles with z-averages between 170-200nm, higher Pdi and zeta potential between +17.6-21.6mV were noticed for the particles produced by ionotropic gelation. Higher encapsulation of insulin of about 90% was achieved using the PEC method as compared to 34% from the ionotropic gelation series. The amount of drug encapsulated in both methods was pH dependent. In vitro xxi glucose dependent insulin release studied on PEC formulations showed a glucose and fructose concentration dependent release which was affected by the buffer system used. Lower insulin release from higher concentration of the sugars was attributed to the formation of bidentate interaction between the diols in the sugar and PBA, which restricts further expansion of the nanoparticles and hence reduces insulin release. This was confirmed by the SEM images of the nanoparticles after exposure to buffer, glucose and fructose in buffers at pH 7.4. Nanoparticles exposed to fructose showed more spherical and intact matrices whilst the buffer samples showed fragmented particles. The samples exposed to glucose showed some degree of fragmentation but not high as compared to that of nanoparticles exposed to buffer. The release of insulin from this formulation was therefore dependent on a complex interplay between the components of the buffer and the amount of sugar present.